Photogalvanic Effect in Mixture of Dyes and Reductant System - Dube, Sangeeta (Asian Journal of Chemistry, 2010)
Photogalvanic effect was observed for system containing mannitol and nitrilotriacetic acid (NTA) as reductant with azure A. azure B and azure C as a mixture of photosensitizers. The photocurrent and photopotential generated by azure A, azure B, azure C and NTA system were 80 μA and 409 m V respectively. Effect of variables on electrical output, fill factor, conversion efficiency and performance of the cell in dark has been studied.